Ruggero Ceppellini: A Perspective on His Contributions to Genetics and Immunology - Bodmer, Walter (Frontiers in Immunology, 2019)
Ruggero Ceppellini, who died at the age of 71 in 1988, was one of the most stimulating and original human geneticists of his generation (1). Ceppellini's outstanding contributions to the genetics of the human blood groups, immunoglobulin allotypes and the HLA system epitomize the study of immunogenetics. By using his considerable skills and insights to unravel the interpretation of the serological data, he made significant contributions to immunology. He is remembered especially for his incisive contributions to the development of the genetics of the HLA system and its nomenclature, including, in particular, his introduction of the term "haplotype", now widely used by geneticists throughout the world, most of whom are unlikely to be aware of its origins.